The Relationship Between Family Support and Students' Interest to Continue Education to SMKN 2 Woyla Aceh - Siti Maryam; Rosmala Dewi; Indani; Siti Wardah (International Conference on Elementary Education, 2023)
Students' interest in continuing education is strongly influenced by parental support. This study aims to determine the relationship between family support and students' interest in continuing their education. The approach used is descriptive quantitative. The population of this study were students of SMPN 1 Woyla and MTSN 5 Aceh Barat Class IX, totaling 95 students with a sample of 95 students. The sampling technique used the formula of Taro Yamane and Slovin. The sampling is done by using purposive sampling technique. Data was collected using questionnaires. The results showed that there was a positive relationship between family support and student interest with a correlation coefficient of 0.334 (p=0.001; p<0.05).